Durability of Near-Complete Skin Clearance in Patients with Psoriasis Using Systemic Biologic Therapies: Real-World Evidence from the CorEvitas Psoriasis Registry - Robert R. McLean; Adam P. Sima; Silky Beaty; Eric A. Jones; Thomas Eckmann; Robert Low; Laura McClung; Rebecca L. Spitzer; Jeffrey Stark; April Armstrong (Adis, Springer Healthcare, 2023)
Abstract Introduction Near-complete skin clearance has become a rapidly achievable treatment goal for patients with psoriasis receiving systemic biologic therapies. However, real-world evidence for durability of near-complete skin clearance and risk factors associated with loss of near-complete skin clearance is limited. Methods This study described durability of near-complete skin clearance (≥ 90% improvement in Psoriasis Area and Severity Index from initiation; PASI90) and identified clinical factors or patient characteristics associated with loss of PASI90 among patients with psoriasis from the CorEvitas Psoriasis Registry (April 2015-August 2021). Included patients had PASI > 5 at biologic initiation and achieved PASI90 at approximately 6 months from initiation (index). A Kaplan-Meier estimate described time to loss of treatment response over 24 months follow-up from index. Proportional hazards regression was used to identify independent predictors of loss of treatment response. Results This study included 687 patient initiations (instances of patients initiating a biologic). Following achievement of PASI90, treatment response was maintained in more than half of patient initiations (54%). Treatment response was maintained at 6, 12, and 18 months from index in an estimated 73% (95% [confidence interval] CI 70-77%), 60% (95% CI 56-63%), and 50% (95% CI 47-54%) of patient initiations, respectively. Adjusted hazards regression suggested non-White race, full-time employment, greater body weight, concomitant psoriatic arthritis, prior use of biologics, and clinically meaningful skin symptoms were associated with loss of treatment response. Conclusions Among real-world patients with psoriasis who achieved PASI90 with biologic therapy, about one-quarter lost response at 6 months, and half lost response at 18 months. Prior use of a biologic therapy and clinically meaningful skin symptoms at index, including itch and skin pain, were associated with loss of treatment response. Therefore, dermatologists may consider focusing on patient-reported symptoms as part of any intervention designed to reduce the likelihood of loss of response to biologic therapies. Trial Registration ClinicalTrials.gov identifier, NCT02707341.